Infection by Mycobacterium bovis in a dog from Brazil - Rocha, Vivianne Cambuí Figueiredo; Figueiredo, Salomão Cambuí de; Rosales, Cesar Alejandro Rodriguez; Porto, Camila Dias; Sequeira, Julio Lopes [UNESP]; Neto, José Soares Ferreira; Paes, Antônio Carlos [UNESP]; Salgado, Vanessa Riesz (Springer Nature, 2017)
Tuberculosis (TB) is a chronic disease caused by bacteria belonging to the Mycobacterium tuberculosis complex (MtbC). This disease rarely affects dogs. Canine infections are usually caused by M. tuberculosis. Mycobacterium bovis infections are rare in dogs and associated with consumption of raw milk or contaminated products. Here, we report a Boxer dog who had a M. bovis infection and was admitted to a Brazilian veterinary hospital with a presumptive diagnosis of chronic ehrlichiosis. Despite receiving treatment for chronic ehrlichiosis, it progressed to death. TB was diagnosed during post-mortem examinations using histopathological analysis. Ziehl-Neelsen staining revealed acid-fast bacilli in the kidneys, liver, mesentery, and a mass adhered to the liver. Further, PCR-restriction analysis was performed to identify mycobacteria in the samples. A restriction profile compatible with MtbC was found in the lungs. In addition, PCR-based MtbC typing deletions at different loci of chromosome 9 enabled the identification of M. bovis in the lungs. Therefore, it is very essential to perform differential diagnosis of TB in dogs with non-specific clinical signs and who do not respond to treatment, particularly those who had been in contact with TB-infected cattle or owners. Further, we highlight the use of molecular methods for the identification of bacilli, improving the diagnosis and aiding epidemiological studies.
Keywords: Dog; Mycobacterium bovis; Tuberculosis